(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2009)
The present investigation was aimed to develop a new formulation containing chemically cross-linked guar gum microspheres loaded with 5-fluorouracil for targeting of colorectal cancer. The emulsification polymerization method involving the dispersion of aqueous phase of guar gum in castor oil was used to prepare spherical microspheres. Cytotoxicity analysis on HT-29 human colon cancer cell lines indicated that 5-FU loaded guar gum microspheres leads to sustained releases of drug and thus delayed apoptosis over a long period of time. In this way, 5-fluorouracil loaded guar gum microspheres have shown promising results in the management of colorectal cancer, warranting thorough in vivo study for scale up technology.